Distribution of enteric protozoan infection among school children in rural and urban areas in West Indonesia: A comparative cross-sectional school-based study - Sari, Ika Puspa; Wahdini, Sri; Herman, Bumi; Sungkar, Saleha (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: The enteric protozoan infection has a high morbidity impact, especially in the pediatric age group. It remains a health problem in tropical countries such as Indonesia due to the limited availability of epidemiological data. This study aims to determine enteric protozoan infection distribution among school children in urban and rural areas in Jakarta-Bogor, Indonesia. Methods: The study was conducted between July and December 2018 involving 812 school children from the Bogor Regency as a rural area and the West Jakarta Administrative City as an urban area. A minimum of 13 students aged 5-10 were sampled through random selection from 30 schools. The enteric protozoa are detected from the observed feces using the direct microscopic examination and the data were processed using the SPSS version 20. Results: The overall prevalence of enteric protozoan infection is 21.8%, with 32.7% and 12.5% in rural and urban areas. It is more dominant in children aged 7-10 at 12.9% compared to those between 5 and 6 at 8.9%. The three dominant protozoa detected in this study are Blastocyctis hominis, Giardia intestinalis, and Entamoeba coli. Entamoeba histolityca and Iodamoeba buetschlii are not identified in the urban area. Conclusions: The prevalence of enteric protozoan infection in children between the ages of 5 and 10 in rural areas is higher than in urban areas. Therefore, interventions such as mass examination of feces followed by antiprotozoal treatment and health education, as well as improvement of sanitation facilities are needed, especially for children living in rural areas.